Isolation, Identification, and Biochemical Characteristics of a Cold-Tolerant Chlorella vulgaris KNUA007 Isolated from King George Island, Antarctica - Seung-Woo Jo; Jeong-Mi Do; Nam Seon Kang; Jong Myong Park; Jae Hak Lee; Han Soon Kim; Ji Won Hong; Ho-Sung Yoon (Journal of Marine Science and Engineering, 2020)
A cold-tolerant unicellular green alga was isolated from a meltwater stream on King George Island, Antarctica. Morphological, molecular, and biochemical analyses revealed that the isolate belonged to the species Chlorella vulgaris. We tentatively named this algal strain C.vulgaris KNUA007 and investigated its growth and lipid composition. We found that the strain was able to thrive in a wide range of temperatures, from 5 to 30 °C; however, it did not survive at 35 °C. Ultimate analysis confirmed high gross calorific values only at low temperatures (10 °C), with comparable values to land plants for biomass fuel. Gas chromatography/mass spectrometry analysis revealed that the isolate was rich in nutritionally important polyunsaturated fatty acids (PUFAs). The major fatty acid components were hexadecatrienoic acid (C16:3 ω3, 17.31%), linoleic acid (C18:2 ω6, 8.52%), and α-linolenic acid (C18:3 ω3, 43.35%) at 10 °C. The microalga was tolerant to low temperatures, making it an attractive candidate for the production of biochemicals under cold weather conditions. Therefore, this Antarctic microalga may have potential as an alternative to fish and/or plant oils as a source of omega-3 PUFA. The temperature tolerance and composition of C.vulgaris KNUA007 also make the isolate desirable for commercial applications in the pharmaceutical industry.